Liraglutide Ameliorates Lipotoxicity-Induced Oxidative Stress by Activating the NRF2 Pathway in HepG2 Cells - Zhu, Chong-gui; Luo, Ying; Wang, Hao; Li, Jun-Yi; Yang, Jie; Liu, Ya-xin; Qu, Hui-qi; Wang, Bao-li; Zhu, Mei (Hormone and Metabolic Research, 2020)
Although glucagon-like peptide-1 (GLP-1) analogue has been reported to suppress oxidative stress in non-alcoholic fatty liver disease (NAFLD), an effective therapeutic agent for NAFLD is currently unavailable. Therefore, in this study, we aimed to investigate the protective effects of the GLP-1 analogue liraglutide against lipotoxicity-induced oxidative stress in HepG2 cells and to elucidate the underlying mechanisms. HepG2 cells were cultured for 48 hours and treated with a free fatty acid (FFA) mixture: FFA mixture and liraglutide or FFA mixture, liraglutide, and exendin (9–39). Lipid accumulation was examined by oil red O staining. Oxidative stress was assessed by measuring the levels of intracellular reactive oxygen species using 2′,7′-dichlorofluorescein diacetate and thiobarbituric acid-reactive substances, whereas antioxidant capacity was assessed by measuring the activity of superoxide dismutase and catalase. Expression of the nuclear factor erythroid-2-related factor 2 (NRF2) gene and the genes encoding antioxidant enzymes was analyzed using quantitative RT-PCR. Cellular and nuclear NRF2 expression levels were assessed using immunofluorescence cell staining and western blotting. Liraglutide treatment reduced high fat-induced lipid formation and the levels of oxidative stress markers and increased antioxidant enzyme activity in HepG2 cells. Liraglutide treatment increased the mRNA expression of NRF2 target genes, induced NRF2 nuclear translocation, and increased nuclear NRF2 levels without altering NRF2 mRNA expression. Collectively, these results indicate that liraglutide exhibits a protective effect against lipotoxicity-induced oxidative stress, possibly via modulation of NRF2 and expression of antioxidant enzymes in liver cells.
Keywords: GLP-1 analogues; antioxidant enzymes; NRF2; NAFLD